ANALISIS ECONOMIC ORDER QUANTITY UNTUK MENENTUKAN PERSEDIAAN BAHAN BAKU KERIPIK SUKUN (Studi Kasus : Industri Rumah Tangga Citra Lestari Production) - Ati, Rosmiati; Rauf, Rustam Abdul; Howara, Dafina (AGROTEKBIS, 2013)
Control of raw materials availability has positive impact to the continuity of production and increase corporate profits, and this also function to the production of breadfruit chips by Citra Lestari, a home industry of breadfruit chip. This study aimed to determine the amount of raw material purchase breadfruit chips were the most economical, knowing the right schedule to buy raw materials to made breadfruit chip and knowing the coming schedule to purchase raw material. The results showed that the use of raw materials to produce chip per period was 4,815 breadfruits year-1 with 140,000 as booking fee and 20,000 IDR as storage cost year-1. Therefore, The most economical was to buy 108 breadfruits for each production cycle, with optimal order frequency was 8 times with lead time of raw materials for 1 week, there were about 207 breadfruits used in a week, safety stock calculated as about 108 fruits for a week if every week there are maximum 250 fruits are needed, with lead time 1 week.